From Werther to Johannes: life as aesthetics - Azevedo, Ricardo Marques de (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2008)
That which art historiography named Romanticism consisted in manifold heterogeneous movements that have spread since the mid-18th century. To characterize these commonly called romantic movements, this essay sets the timeline to a period between the publication of two novels written in the first person of the singular and in the form of a diary: Werther and Diary of a seducer. If, in Goethe, passion consumes the main character, seduction in Kierkegaard's text is only artifice and calculation. Although neither a coherent artistic program nor a characteristic lyric or figurative norm is consolidated in this period, a peculiar sensibility permeates artistic poetics. It is supposed then that the work of art is corollary or emanation of a life, itself artistic, and comprehensive and minute aesthetics of existence take place.